Biofilm formation behaviour of marine filamentous cyanobacterial strains in controlled hydrodynamic conditions - Romeu, Maria J.; Alves, Patrícia; Morais, João; Miranda, João M.; Jong, Ed.D.; Sjollema, Jelmer; Ramos, Vítor; Vasconcelos, Vitor; Mergulhão, Filipe J. M. (Environmental microbiology, 2019)
Summary Marine biofouling has severe economic impacts and cyanobacteria play a significant role as early surface colonizers. Despite this fact, cyanobacterial biofilm formation studies in controlled hydrodynamic conditions are scarce. In this work, computational fluid dynamics was used to determine the shear rate field on coupons that were placed inside the wells of agitated 12‐well microtiter plates. Biofilm formation by three different cyanobacterial strains was assessed at two different shear rates (4 and 40 s−1) which can be found in natural ecosystems and using different surfaces (glass and perspex). Biofilm formation was higher under low shear conditions, and differences obtained between surfaces were not always statistically significant. The hydrodynamic effect was more noticeable during the biofilm maturation phase rather than during initial cell adhesion and optical coherence tomography showed that different shear rates can affect biofilm architecture. This study is particularly relevant given the cosmopolitan distribution of these cyanobacterial strains and the biofouling potential of these organisms.